DETERMINATION OF OPTIMUM PERIOD OF CONTROL OF TECHNICAL BEING OF VERTICAL VALC MILL AG-MPS 180BK - Заміховський, Леонід Михайлович; Зікратий, Сергій Вікторович; Зікратий, Ростислав Богданович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Procedure of determination of optimum intercontrol period of the technical being of working organs of mill of AG-MPS 180BK – milling valcs and racecourse of milling bowl is examined, by the method of parametric idenentication after the specified transitional description of mill.